Pragmatics and Pedagogy: Illocutionary Acts in “Jackie” Movie and their Merdeka Belajar Curriculum Relevance - Zelfany Lufti Milinia Adira Putri; Wiwin Widyawati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Illocutionary acts, as theorized by Kent Bach, play a crucial role in daily communication by conveying the speaker's intent beyond mere words. These big four acts, which include Constative, Directives, Commisives, and Acknowledgement, help people understand the social and pragmatic context of interactions where in Merdeka Belajar Curriculum, which emphasizes independence and critical thinking in education, understanding illocutionary acts can be linked to social norms by fostering effective communication skills. Students learn to interpret and employ various speech acts appropriately, aligning their verbal interactions with societal expectations and cultural norms.The study aims to analyze the illocutionary acts used by the main character in the movie